HBV-INFECTION DE NOVO AFTER ORTHOTOPIC LIVER TRANSPLANTATION: CLINICAL AND VIROLOGICAL CHARACTERISTICS, ASSESSMENT OF ANTIVIRUS THERAPY EFFECTIVENESS - O. I. Malomuzh; E. V. Chekletsova; X. M. Кhizroyev; V. A. Pets; S. V. Fokin; V. A. Taranov; O. M. Tsirulniкova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2012)
We studied 11 cases of HBV-infection de novo in patients after orthotopic liver transplantation performed because of non-viral cirrhosis. Serum НBeAg, was revedled in all patients. In most cases clinical course of HBV-infection was benign. Treatment with entecavir was more effective than lamivudin, and brought to НBsAg elimination in 4 patients. Treatment with lamivudin led to descrease viral load in all patients and HBsAg elimination in one case.